Enantioselective Biginelli Reaction of Aliphatic Aldehydes Catalyzed by a Chiral Phosphoric Acid: A Key Step in the Synthesis of the Bicyclic Guanidine Core of Crambescin A and Batzelladine A - Guo, Yongbiao; Gao, Zhenhua; Fan, Chongxu; Chen, Jisheng; Li, Junchen; Huang, Yongpeng; Huang, Guilan; Yu, Huilan; Zou, Chuanpin (Synthesis, 2018)
An efficient chiral phosphoric acid catalyzed Biginelli reaction for the synthesis of optically pure 4-alkyl-3,4-dihydropyrimidin-2-(1H)-ones has been developed, with a wide range of the desired products being obtained in moderate to high yields with good to excellent enantioselectivities (up to >99% ee after one recrystallization). The synthetic utility of this reaction is illustrated in various aliphatic bicyclic guanidine compounds, which is applied in the formal synthesis of the bicyclic guanidine core of crambescin A and batzelladine A.
Keywords: Biginelli reaction; dihydropyrimidinone; aliphatic aldehydes; crambescin; batzelladine